COMPARISON OF EFFICACY OF 1-WEEK ORAL AZITHROMYCIN WITH 2-WEEK TOPICAL 1% AZITHROMYCIN EYE DROPS IN THE TREATMENT OF POSTERIOR BLEPHARITIS - Ahmad, Adnan; Mubashir Rehman (Journal of Postgraduate Medical Institute, 2022)
Objective: To assess the efficacy of 1-week of oral azithromycin (AM) with 2 weeks of topical azithromycin eye drops in posterior blepharitis patients. Methodology: In this quasi-experimental study, 80 participants were enrolled (>45 years old) with meibomian gland dysfunction (MGD) at the Department of Ophthalmology, Qazi Hussain Ahmed Medical Complex, Nowshera from January to September 2020. Patients were allocated to get either 1-week of oral azithromycin (500mg/day) or 2 weeks of continued topical azithromycin 1% once daily. A scoring system was devised which included 5 symptoms and 7 signs which were assessed at baseline and follow-ups on 1st, 2nd, and 4th-week post-therapy. The total score was documented at the end of the study by summing up the symptoms and signs score. Results: The objective and subjective features of the disease showed improvement with either therapy, however, 2 weeks of topical azithromycin 1% once a day showed significantly more improvements (p= 0.008). We observed improvement in the symptoms of disease in both groups but that didn’t achieve the level of statistical significance between the groups (0.242). Systemic side effects in the form of anorexia, nausea, and gastrointestinal upsets were negligible in topical Azithromycin as compared to its oral form. Conclusion: Both oral and topical forms of drugs effectively ameliorated the symptoms of posterior blepharitis, however, 2 weeks of topical azithromycin 1% once a day also addressed the signs of the disease along with benefits of having better tolerance (least gastrointestinal upsets) leading to improved compliance in comparison to its oral form.